Indonesia’s Public Diplomacy in Increasing the Number of Visits of Singapore Tourists - Sherina Amellia; Asep Kamaluddin Nashir; Rizky Hikmawan (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
Singapore is the most significant contributor to tourist visits to Indonesia, but in 2015-2016, the number of tourist visits from Singapore decreased from around 1,59 million people to 1,51 million people. This study aims to determine the efforts of Indonesia's public diplomacy in increasing the number of tourist visits from Singapore through Wonderful Indonesia as nation branding. This research is focused on 2016 to 2019. This research used a descriptive qualitative method by using data collection techniques in the form of interviews, and document collection, such as official documents from private sources and internet sources in the form of articles in relevant journals and publications, and can be ascertained their validity. The author also uses three stages of data analysis according to Miles and Huberman (1994), including data reduction, data presentation, and drawing conclusions or data verification by data triangulation to explain the data obtained from the field in detail and clearly. The study found that Indonesia's public diplomacy efforts, which involved non-state actors by promoting Wonderful Indonesia, had a positive impact on tourism from Singapore. These efforts not only increased the number of tourist visits, but also boosted the country's foreign exchange income and earned recognition for the actors involved. Overall, the objective of these initiatives was to promote Indonesian culture, foster good relations with the Singaporean public, and create a favourable impression of Indonesia as a tourist destination. However, this promotional activity still has several obstacles due to the lack of infrastructure conditions in Indonesia around tourist destinations and Indonesia's level of security, as well as a small promotion budget.